Postage stamp commemorating German porcelain, German Democratic Republic - Gruner, Erich
Stamp from the series on the Leipzig Spring Trade Fair in 1950. Commemorates first porcelain on the trade fair in 1710.
Keywords: Postage stamps; Germany (East); Trade shows; Commemorative postage stamps; Science on postage stamps; Porcelain, German